2015
DOI: 10.21101/cejph.a4177
|View full text |Cite
|
Sign up to set email alerts
|

Age and Gender Differences in Prevalence of Screen Based Behaviour, Physical Activity and Health Complaints among Slovak School-aged Children

Abstract: SUMMARYAim: The aim of this study was to assess age and gender differences in prevalence of screen based behaviour, physical activity and health complaints among Slovak school-aged children.Methods: Data from the cross-sectional Health Behaviour of School-aged Children study collected in 2010 among Slovak children (age 11-15 years, N = 8,042) was used. Logistic regression models adjusted to age and gender were used to analyse the associations between watching TV, working with a computer or playing computer gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…A study reports that gender differences are significant in prevalence of screen- based behavior except in the television viewing [39]. Logistic regression analysis also shows that television viewing >2 h a day was significantly associated with video games >2 h a day and Internet use >2 h a day.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A study reports that gender differences are significant in prevalence of screen- based behavior except in the television viewing [39]. Logistic regression analysis also shows that television viewing >2 h a day was significantly associated with video games >2 h a day and Internet use >2 h a day.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies found that male adolescents were less likely to report poor/fair self-rated health and health complaint as compared to female [19,39]. Adolescents conceptualize health as a construct related to medical, psychological, social, and lifestyle factors [42]; which may have an influence on gender.…”
Section: Discussionmentioning
confidence: 99%
“…During childhood and adolescence, subjective somatic and psychological complaints such as headaches, stomach aches, backaches, feeling dizzy, feeling low, being irritated, feeling nervous or having difficulties in sleeping are common [1]. Subjective health complaints increase with rising age, mainly among girls and youth from lower socioeconomic status [2,3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…More than half of school-aged children exceed recommended time spent on screen-based activities, and adolescents with chronic conditions were rather similar to their peers. Other studies on children have also shown an increased amount of time devoted to screen-based activities [ 33 , 34 ]. This pattern of spending their leisure-time thus seems to be a general trend characteristic for this young generation.…”
Section: Discussionmentioning
confidence: 99%